70.7k views
3 votes
Question 8
Calculate the difference (4x2 + x - 5) – (5x2 - 1).

1 Answer

5 votes

Answer:

x - 6

Explanation:

(4x2 + x - 5) - (5x2 - 1)

According to the order of operations, parenthesis come first so we will solve what is in the parenthesis first.

Then we do the multiplication because it comes before addition and subtraction.

4x2 = 8

Now we have 8 + x - 5

Combine like terms and 8-5=3 so we have 3 + x

Now for the second one.

5x2=10

10-1=9

Subtracting this from the first expression we have:

3+x-9 =

x - 6

User Rockbot
by
6.1k points